COVID-19 Vaccines Current State and Perspectives - Abdurakhmonov, Ibrokhim Y. (IntechOpen, 2023)
COVID-19 Vaccines - Current State and Perspectives provides the reader with the latest overview and opinions on the current state of the art in COVID-19 vaccines, as well as future prospects. The challenges covered include novel vaccine development for the emerging variants of concern (VOCs), vaccine side-effects with real-world examples, population hesitancy, and country experiences with COVID-19 vaccine development, clinical trialing and mass vaccination. Chapters discuss new opinions and directions on the repurposing of existing traditional vaccines with a wide spectrum of action and new platforms for fast-tracked vaccine production and approvals.